Makna Keselamatan Dalam Hukum Taurat Bagi Kehidupan Orang Percaya Masa Kini - Sabda Budiman; Kristian Karipi Takameha (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2022)
Soteriology is a very important discussion in the Bible. The discussion of soteriology is a broad discussion. Almost all parts of the book contain the doctrine of salvation. Christians need to understand the meaning of the doctrine of salvation in the Old Testament and draw implications from the meaning of that doctrine of salvation. This study examines the doctrine of salvation in the Old Testament and the meaning of the doctrine of salvation in the Old Testament for the lives of today's believers. This study aims to explain the meaning of the doctrine of salvation in the Old Testament and its efficacy for today's believers. The authors used qualitative research methods with a descriptive approach. The meaning of the doctrine of salvation in the Old Testament for today's believers is to obey God's commandments, have a sincere heart, and live pleasing to God. Soteriologi (doktrin keselamatan) merupakan pembahasan yang sangat penting di dalam Alkitab. Pembahasan tentang soteriologi merupakan pembahasan yang luas. Hampir di dalam seluruh bagian kitab mengandung doktrin tentang keselamatan. Orang Kristen perlu memahami makna ajaran keselamatan dalam Perjanjian Lama dan menarik implikasi dari makna ajaran keselamatan tersebut. Penelitian ini mengkaji ajaran keselamatan di dalam Perjanjian Lama dan makna ajaran keselamatan dalam Perjanjian Lama bagi kehidupan orang percaya masa kini. Penelitian ini bertujuan untuk memaparkan makna ajaran tentang keselamatan dalam Perjanjian Lama dan imlikasinya bagi orang percaya masa kini. Penulis menggunakan metode penelitian kualitatif dengan pendekatan dekriptif. Adapun makna ajaran keselamatan dalam Perjanjian Lama bagi orang percaya masa kini ialah taat kepada perintah Allah, memiliki hati yang tulus, dan hidup berkenan kepada Allah.